The thermochemicals behaviour of oil palm shell wastes and coal blends and its circulating fluidized bed - Ahmad Hussain, author; Farid Nasir Ani, 1957-, author; Amer Nordin Darus, author; Mohammad Khalid Wahid, author; Hamdan Mokhtar, author; Saiful Azam, author; Norzalia Sulaiman, author; Azeman Mustafa, 1966-, author (Skudai : Universiti Teknologi Malaysia)
PSZJBL